Microprofiles of oxygen, redox potential, and pH, and microbial fermentation products in the highly alkaline gut of the saprophagous larva of Penthetria holosericea (Diptera: Bibionidae) - Šustr, Vladimír; Stingl, Ulrich; Brune, Andreas (Journal of insect physiology, 2014)
The saprophagous larvae of bibionid flies harbor bacteria in their alkaline intestinal tracts, but little is known about the contribution of the gut microbiota to the digestion of their recalcitrant diet. In this study, we measured oxygen and hydrogen partial pressure, redox potential and pH in the midgut, gastric caeca and hindgut of larvae of the bibionid fly Penthetria holosericea with Clark-type O2 and H2 microsensors, platinum redox microelectrodes, and LIX-type pH microelectrodes. The center of the midgut lumen was anoxic, whereas gastric caeca and hindgut were hypoxic. However, redox potential profiles indicated oxidizing conditions throughout the gut, with lowest values in the midgut (+20 to +60mV). Hydrogen production was not detected. The midgut was extremely alkaline (pH around 11), whereas hindgut and gastric caeca were neutral to slightly alkaline. While HPLC analysis showed high concentrations of glucose in the midgut (15mM) and gastric caeca (27mM), the concentrations of microbial fermentation products such as lactate (2-4mM), acetate (<1mM) and succinate (<0.5mM) were low in all gut regions, suggesting that the contribution of microorganisms to the digestive process, particularly in the alkaline midgut, is only of minor importance. We conclude that the digestive strategy of the saprophytic larva of P. holosericea, which feeds selectively on decomposed leaves and its own microbe-rich faeces, differs fundamentally from those of detritivorous and humivorous insects, which host a highly active, fermentative microbiota in their alkaline midgut or hindgut compartments.
Keywords: Feces; Bacteria; koncentrace vodíkových iontů; trávicí systém; Hydrogen; Hydrogen-Ion Concentration; zvířata; gastrointestinální trakt; feces; larva; Fermentation; Gastrointestinal Tract; kyslík; Diptera; Oxygen; fermentace; Oxidation-Reduction; Animals; Digestive System; oxidace-redukce; vodík; Larva